Unusual Path of Branches of Ilioinguinal Nerve: A Clinically Important Anatomic Variant. - Satheesha BN,; Srinivasa RS,; Prakashchandra S,; Surekha DS,; Deepthinath R,; Raghu J,; Abhinitha P,; Jyothsna P, (Department of Surgery, UKM Medical Centre, 2014)
Ilioinguinal nerve is a collateral branch of lumbar plexus. Its anatomical variations in relation to adjacent musculoaponeurotic structures play a crucial role in the development of neuropathies associated with lower abdominal surgeries. In this report, we present a rare case of unusual course and branches of the ilioinguinal nerve, in a 55-year-old male cadaver. In the lateral part of inguinal canal ilioinguinal nerve gave three branches. Two of its branches pierced the external oblique aponeurosis, about 6 cm above the pubic symphysis, to supply the skin of the lower part of the anterior abdominal wall. Another branch pierced the conjoint tendon, in the medial part of the inguinal canal about 2 cm above the superficial inguinal ring. Knowledge of unusual path of these branches may be important to avoid injuries during the surgical repair of groin hernias. Further care should be taken while dealing with the conjoint tendon in the Bassini procedure.